Association of triglyceride glucose index as insulin resistance measure and waist to hip ratio in apparently healthy students of University of Sarajevo - Sabaheta Hasić; Aida Đozo; Emina Kiseljaković; Radivoj Jadrić; Lamija Mlaćo; Amil Topuz; Selma Hasić (Medicinski glasnik, 2025)
Aim: This study aimed to reveal the prevalence of the insulin resistance (IR) identified by triglyceride glucose index (TyG index) among students of University of Sarajevo. The impact of visceral fat level and waist to hip ratio measures on TyG value in students has been investigated. Patients and methods. Study included 160 apparently healthy students, both genders, aged from 19-27 years. Two groups were formed: Group1, TyG <4,49 and Group 2, TyG³4,49. A short interview, questionnaire, anthropometric measures, visceral fat level (VFL), blood pressure and biochemical parameters were applied. The statistical level of significance was P<0,05. Results: . Forty-five students (28, 1%) were insulin resistant. There was a significant difference in TyG value (P<0,001), [group 1- 4,19 (3,93-4,34 vs. group 2 - 4,59 (4,55-4,74)]. Fasting blood glucose (FBG) and lipid parameters-total cholesterol, triglycerides and very low-density lipoprotein cholesterol (TC, TG and VLDL-C) were significantly higher in group TyG ³4,49 compared to TyG <4,49 group, with exception of HDL-C of LDL-C (P>0.05). Stepwise linear regression analysis showed significant impact of waist to hip ratio on TyG value (P=0,001). Conclusion: The prevalence of IR measured by TyG in university students was 28,1%. The impact of waist to hip ratio on value of TyG index points on possible application of both parameters in visceral obesity and insulin resistance assessment in apparently healthy individuals.
Keywords: blood glucose; triglycerides; obesity; prevalence